2005
DOI: 10.1038/sj.hdy.6800752
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow and hybridisation in a mixed oak forest (Quercus pyrenaica Willd. and Quercus petraea (Matts.) Liebl.) in central Spain

Abstract: Oaks are long-standing models for the study of gene flow and hybridisation. Temperate (Quercus petraea) and subMediterranean (Quercus pyrenaica) oaks coexist in central Spain, showing remarkable differences in population size and structure. Q. petraea has a scattered distribution in central Spain, where it is at one of the southernmost limits of its range, and forms low-density stands; in contrast, Q. pyrenaica is widespread in the region. We selected a mixed population of the two species (B13 ha, 176 adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
3
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 36 publications
6
105
3
10
Order By: Relevance
“…In two studies carried out on the wind-dispersed conifer P. pinaster, GonzalezMartinez et al (2002GonzalezMartinez et al ( , 2006 found mean seed dispersal distances ranging from 26.53 m to 58.16 m, but P. pinaster has heavier seeds that limit its dispersion and their studied area was smaller. In three oak species mean seed dispersal distances detected by means of parentage analysis ranged between 14 and 42 m, but in these species dispersal is mainly determined by gravity, and the rare LDD events are caused by birds and rodents (Dow and Ashley, 1996;Valbuena-Carabañ a et al, 2005). Our results can be explained considering the low mass (B10 mg) of P. abies seeds and their seed wing (Bernetti, 1995).…”
Section: Discussionmentioning
confidence: 66%
“…In two studies carried out on the wind-dispersed conifer P. pinaster, GonzalezMartinez et al (2002GonzalezMartinez et al ( , 2006 found mean seed dispersal distances ranging from 26.53 m to 58.16 m, but P. pinaster has heavier seeds that limit its dispersion and their studied area was smaller. In three oak species mean seed dispersal distances detected by means of parentage analysis ranged between 14 and 42 m, but in these species dispersal is mainly determined by gravity, and the rare LDD events are caused by birds and rodents (Dow and Ashley, 1996;Valbuena-Carabañ a et al, 2005). Our results can be explained considering the low mass (B10 mg) of P. abies seeds and their seed wing (Bernetti, 1995).…”
Section: Discussionmentioning
confidence: 66%
“…However, the Mediterranean basin is home to over two-dozen little studied white oak species (Amaral Franco, 1990;Denk and Grimm, 2010), many of them with restricted distribution ranges and little economic importance, but with a prominent ecological role. These species show evidences of recurrent and ongoing gene flow, as indicated by the sharing of chloroplast DNA variants with strong biogeographic structure (Olalde et al, 2002;Petit et al, 2002) and by the occurrence of hybrid/admixed trees in sympatric populations (Valbuena-Carabaña et al, 2005;Curtu et al, 2007;Lepais and Gerber, 2011). Furthermore, all our data suggest their genomes maintain a large degree of synteny (Casasoli et al, 2006;Bodénès et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…The exclusion probabilities for the microsatellites are high and theoretically 4-6 loci are fully adequate to determine parentage (Valbuena-Carabana et al, 2005;Dow and Ashley, 1996). Taking into account the high exclusion probabilities, the nature of a relatively isolated stand and the high frequency of fathers found, cryptic gene flow in this study was assumed to be low and was therefore not calculated.…”
Section: Molecular Datamentioning
confidence: 99%